Thermodynamic stability of coke-generating compounds formed on the surface of platinum dehydrogenation catalysts in their oxidation with water; Petroleum Chemistry; Vol. 53, iss. 4 - Kravtsov A. V. Anatoly Vasilyevich; Ivanchina E. D. Emilia Dmitrievna; Ivashkina E. N. Elena Nikolaevna; Frantsina E. V. Evgeniya Vladimirovna; Kiseleva S. V.; Romanovskiy R. V. Rostislav Vladimirovich (2013, 2013)
Title screen